HUBUNGAN KEBIASAAN MEROKOK DENGAN KEJADIAN TB PARU DI RUANG PARU RSUD TENGKU MANSYUR KOTA TANJUNGBALAI TAHUN 2019 - KASMINAH . (JURNAL ILMIAH KOHESI, 2021)
The purpose of this study was to identify the relationship of smoking habits with the incidence of pulmonary TB in thepulmonary room of Tengku Mansyur Hospital in Tanjungbalai City. This type of research is correlational i.e. research orresearch the relationship between two variables in a situation or a group of subjects, using a cross sectional approach. Thisresearch was conducted at Tengku Hospital in Tanjungbalai. The sample of this study amounted to 24 people. Analaisisresults were known to respondents who achieved high smoking habits as many as 16 people (64.0) while respondents withmoderate smoking habits amounted to 8 people (36.0). Thus, the majority of respondents studied from 24 respondentsachieved a high smoking habit of 16 people (36.0). The respondents studied the majority had a high incidence of PulmonaryTB which amounted to 18 (72.0%), while the respondents with low TB incidence amounted to 6 (28.0%). Thus, the majorityof respondents had high TB incidence of 18 (72.0%). Based on statistical test, obtained p-value of 0.003 thus thesignificance value of p-value 0.003 > (0.05) then H0 received and Ha rejected which means there is a significant relationshipbetween smoking habit and pulmonary TB incidence in the lung room of Tengku Mansyur Hospital Tanjungbalai City In 2019.